2022
DOI: 10.1080/15384047.2022.2042160
|View full text |Cite
|
Sign up to set email alerts
|

Targeting long non-coding RNA PVT1/TGF-β/Smad by p53 prevents glioma progression

Abstract: Glioma is a primary intracranial malignant tumor with poor prognosis, and its pathogenesis is unclear. This study discussed the impact of p53/lncRNA plasmacytoma variant translocation 1 (lncRNA PVT1)/transforming growth factor beta (TGF-β)/Smad axis on the biological characteristics of glioma. Glioma and normal tissues were collected, in which relative lncRNA PVT1 and p53 expression was assessed. Pearson’s analysis was adopted for the correlation analysis between lncRNA PVT1 and p53. Short interfering RNA (siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Synthetic cancer-sensing circuits have been designed to recognize cancer cells based on intracellular gene expression profiles [ 8 , 11 ]. PI3K pathway inhibitors loaded with liposomes, cationic liposomes containing the TP53 gene plasmid, siRNAs against EGFR and PDGFRA, siRNAPVT1, siRNAp53, siRNASTAT3, and PDL1 have been investigated for glioma therapy [ 40 , 41 , 42 ]. Multi-colored RNA circuits (generating tumor suppressor microRNAs targeting key glioma driver genes) have been employed in nanohydrogels to produce the circuit’s logical synthetic genetics.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic cancer-sensing circuits have been designed to recognize cancer cells based on intracellular gene expression profiles [ 8 , 11 ]. PI3K pathway inhibitors loaded with liposomes, cationic liposomes containing the TP53 gene plasmid, siRNAs against EGFR and PDGFRA, siRNAPVT1, siRNAp53, siRNASTAT3, and PDL1 have been investigated for glioma therapy [ 40 , 41 , 42 ]. Multi-colored RNA circuits (generating tumor suppressor microRNAs targeting key glioma driver genes) have been employed in nanohydrogels to produce the circuit’s logical synthetic genetics.…”
Section: Resultsmentioning
confidence: 99%
“…p53 inhibits glioma cell proliferation, migration and invasion,which stops tumor growth, and induces apoptosis by downregulating PVT1 expression. PVT1 binds to TGF-β to activate the TGF-β/Smad signaling pathway to promote glioma progression [12] . ITGB1-DT is overexpressed in gastric adenocarcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple projects have shown that lncRNAs are associated with the prognosis and the growth of cancer cells [12][13][14][15] . Glioma tissues and cells showed signi cant downregulation of p53 expression and a signi cant increase in lncRNA PVT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, lncPVT1 influence bone morphogenetic protein (BMP) signaling pathway by regulating miR-128-3p/GREM1 axis, thereby promoting glioma cell proliferation, invasion, migration, and antiapoptosis (112). A recent study showed that tumor suppressor gene p53 inhibits glioma cell proliferation, migration, and invasion while inducing apoptosis by blocking lncPVT1/TGFb/Smad signaling pathway (113). Researchers knocked down lncPVT1 expression levels in SHG-44 glioma cells, added different concentrations of paclitaxel, and then measured their apoptosis rate.…”
Section: Gliomamentioning
confidence: 99%